Penerapan Konsep Bawah Laut pada Interior Selam Rekreasi di Surabaya - Gunawan, Edbert (Intra, 2014)
Interior Design of Recreational Scuba Training in Surabaya is a means that aims to meet the needs of the knowledge and training of divers. The background design is Surabaya city does not yet have a dedicated facility for dive training. The scope of this design as an area galleries, stores, cafes, travel, cinema, classroom training, office and support training area. The concept of "GROWTH" is used in the design, which is inspired by coral reefs which always grow to be larger. Theme design atmosphere: "UNDER THE SEA" is transformed into a training facility with interior design elements and character as are in the sea.